Enhanced Optical Characteristics and Low Energy Gap of SrTiO3 Doped Polymeric Blend for Optoelectronics Devices. Issue 1 (July 2021) - Hadi, Abeer Ghalib; Al-Ramadhan, Zainab; Hashim, Ahmed
Abstract: Films of PVA/PAA/SrTiO3 nanostructures were prepared for flexible optoelectronic devices. Studying the optical characteristics of PVA/PAA/SrTiO3 films were tested. The results showed the improving of the optical characteristics of (PVA/PAA) mixtures by the increase in SrTiO3 NPs content. Also, results showed the energy gap of PVA/PAA mixtures decreased from to with adding of SrTiO3 NPs. Finally, the results indicated to the PVA/PAA/SrTiO3 nanostructures may be used in various optoelectronic devices.